Mushrooms Cultivation Training From Corn Cobs Waste as an Effort to Improve The Economy of Rural Communities - Anggia Kalista; Any Dian Murdiniyati; Dafa Maulana; Winda Refian Oktafiani; Dimas Maulana (Kontribusia : Research Dissemination for Community Development, 2023)
Wukirharjo is a village that has potential in the field of maize crop agriculture, corn is a plant that is taken from the seeds and leaves the skin and cob. In Wukirharjo, corn cobs are only used as fuel and some are traded. Corn cobs can be used appropriately and will be of very high value and benefit the community itself, one of which can be used as a medium for corn cob mushrooms. The mushrooms produced can be consumed alone or traded in large markets. Based on the above problems the authors took the initiative to provide assistance to the village of Wukirharjo, Parengan District, Tuban Regency with the aim of utilizing and holding “Training for Making Corn Cob Mushrooms”. The use of the corn cob itself to reduce agricultural waste, as corn commodities. This service aims as basic knowledge for community empowerment through the use of waste in Wukirharjo village as well as ways to develop the potential of natural resources in the village. This service in the form of assistance, in addition to partnering with the village head of Wukirharjo and his staff, also with PKK women and Posyandu cadres in Wukirharjo village. The method applied in this service is by providing assistance and training at the local Village Hall. The expected result of this service is as a motivation for the community to be more creative in their work through the use of goods or waste around them so that they have economic value that can spur a better economy and support the welfare of the people in Wukirharjo village. This service can be said to be successful when there is a change in people's knowledge and skills regarding formulation, making growth media, and mushroom cultivation techniques using corn cobs.